2009
DOI: 10.11645/3.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Learning by Doing –

Abstract: By 'open access' to this literature, we mean its free availability on the public internet, permitting any users to read, download, copy, distribute, print, search, or link to the full texts of these articles, crawl them for indexing, pass them as data to software, or use them for any other lawful purpose, without financial, legal, or technical barriers other than those inseparable from gaining access to the internet itself. The only constraint on reproduction and distribution, and the only role for copyright i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Librarians are always looking for ways to make IL teaching more diverse, with Ross and Furno (2011) suggesting that finding the best pedagogical practices is an iterative process that takes patience and courage to fail. There is a trend towards making the delivery of IL education an active learning experience (Bell, 2007;Boss et al, 2015;Hegarty et al, 2009;Holderied, 2011;Lahlafi et al, 2012). Active learning refers to any learning activity which involves active participation of the student (Higher Education Academy, 2008), rather than the one-way communication between teacher and student characteristic of passive teaching methods (Holderied, 2011).…”
Section: Active Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Librarians are always looking for ways to make IL teaching more diverse, with Ross and Furno (2011) suggesting that finding the best pedagogical practices is an iterative process that takes patience and courage to fail. There is a trend towards making the delivery of IL education an active learning experience (Bell, 2007;Boss et al, 2015;Hegarty et al, 2009;Holderied, 2011;Lahlafi et al, 2012). Active learning refers to any learning activity which involves active participation of the student (Higher Education Academy, 2008), rather than the one-way communication between teacher and student characteristic of passive teaching methods (Holderied, 2011).…”
Section: Active Learningmentioning
confidence: 99%
“…Many previous studies use ARSs to examine the effectiveness of active learning, against traditional lecture based teaching (Holderied, 2011;Ross & Furno, 2011;Walker & Pearce, 2014). It has been shown that active learning approaches are effective in IL teaching (Bell, 2007;Boss, Angell, & Tewell, 2015;Hegarty, Carbery, & Hurley, 2009;Holderied, 2011;Lahlafi, Rushton, & Stretton, 2012), and so this study aims to go beyond the existing research by specifically examining the effectiveness of these tools as part of an active learning pedagogy. Initially the study aimed to address two main questions:…”
Section: Introductionmentioning
confidence: 99%